The improved corrosion resistance of sputtered CrN thin films with Cr-ion bombardment layer by layer. (September 2017) - Wang, Desheng; Hu, Ming; Jiang, Dong; Fu, Yanlong; Wang, Qinqin; Yang, Jun; Sun, Jiayi; Weng, Lijun
Abstract: The sputtered CrN coatings, which were bombarded by the energetic Cr-ion via filtered arc ion plating layer by layer, were prepared to improve the corrosion resistance of the coated samples. By controlling the times of Cr ion bombardment, the influence of the Cr ion bombarding of the sputtered CrN were investigated from the aspect of the microstructure and corrosion behavior. The results indicated that the CrN film showed a suppressed effect on the coarse columnar structure and a more compact structure with lower porosity by introducing the Cr-ion bombardment. Potentiodynamic polarization curves showed that the CrN coated samples had an obvious improved corrosion resistance after the energetic Cr ion bombardment. With the bombarding times of Cr ion increasing from four to ten, the corrosion resistance of CrN coated samples showed a further improvement with corrosion potential increased about 100 mV and the corrosion current density decreased more than one order of magnitude when compared with the non-bombarded CrN coating. Highlights: Sputtered CrN coatings bombarded by the energetic Cr ion periodically via filtered arc ion plating were prepared. Cr ion bombardment can effectively suppress coarse columnar grain growth of the as-deposited CrN coatings. CrN coated samples showed an obvious improvement of corrosion resistance by introducing the energetic Cr ion bombardment.